(untitled) (Tạp chí Y học Cộng đồng, 2026)
Introduction: COVAX is a key part of the Access to COVID-19 Tools (ACT) Accelerator, significantly contributing to Vietnam’s COVID-19 vaccination coverage during the pandemic peak in 2021-2022. This study analyzes COVAX’s impact and offers recommendations for improvement. Methods: Data were collected through online interviews and document reviews in August-September 2022, involving 15 key informants from major stakeholders in Vietnam’s COVID-19 vaccination program. Results: COVAX supplied vaccines to approximately 35% of Vietnam’s population, but the country was excluded from discussions on program design and distribution strategies. This oversight led to ineffective planning for vaccine distribution. Conclusion: Vietnam needs to proactively prepare and streamline the administrative processes for vaccine approval and distribution in future pandemics.